2020
DOI: 10.3390/ijerph17103451
|View full text |Cite
|
Sign up to set email alerts
|

Early-Life Conditions and Cognitive Function in Middle-and Old-Aged Chinese Adults: A Longitudinal Study

Abstract: A range of previous studies have suggested that early-life conditions (ELCs) are associated with various health problems throughout life in Western societies. The aim of this study was to investigate whether, and how, early-life conditions predicted the level and trajectory of cognitive function in middle- and old-aged Chinese adults. Data were obtained from China Health and Retirement Longitudinal Study which comprised 16,258 adults at baseline. Cognitive function was assessed using mental intactness and epis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 49 publications
(70 reference statements)
3
25
0
Order By: Relevance
“…Overall, the association of childhood socioeconomic status and height with cognitive functioning was significant in India and China, suggesting the similarities in the association of childhood socioeconomic status and height in determining later life cognitive functioning. The results of this study on the association between parental education and later life cognitive functioning are consistent with the findings of previous studies conducted in China and South Africa suggesting the long-term effect of childhood circumstances in developing countries [27,28,31,32]. We also observed lower cognitive functioning score among older adults whose parents had no schooling across different ages which highlighted the role of childhood circumstances; this is consistent with previous literature [50].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Overall, the association of childhood socioeconomic status and height with cognitive functioning was significant in India and China, suggesting the similarities in the association of childhood socioeconomic status and height in determining later life cognitive functioning. The results of this study on the association between parental education and later life cognitive functioning are consistent with the findings of previous studies conducted in China and South Africa suggesting the long-term effect of childhood circumstances in developing countries [27,28,31,32]. We also observed lower cognitive functioning score among older adults whose parents had no schooling across different ages which highlighted the role of childhood circumstances; this is consistent with previous literature [50].…”
Section: Discussionsupporting
confidence: 92%
“…Childhood socioeconomic status plays an important role in determining the higher educational attainment, immunisation, health, and nutrition which have a significant impact in later life [20][21][22][23]. Studies mainly from high-income countries showed strong association of adverse childhood circumstances such as poor socioeconomic status, and childhood poverty/deprivation with poor cognitive functioning, cognitive impairment, and dementia [24][25][26][27][28][29][30][31]. However, very few studies have examined the association between life course socioeconomic status and cognitive functioning in low and middleincome countries [32].…”
Section: Introductionmentioning
confidence: 99%
“…The results of this study are consistent with previous studies conducted on the association between parental education and later life cognition suggesting the long-term effect of childhood circumstances in developing countries such as China and South Africa (31,32,35,41). We also observed a faster decline of cognitive functioning among older adults whose parents had no schooling which highlighted the role of childhood circumstances across different age period as consistent with previous literature (61).…”
Section: Discussionsupporting
confidence: 92%
“…Childhood circumstance is one of the key factors in determining cognitive functioning across the life course and play important role in determining cross-national subgroup level variations (27,28). Studies mainly from high-income countries showed a strong association of childhood circumstances such as poor socioeconomic status, and childhood poverty deprivation with cognitive functioning, cognitive impairment, and dementia (24,(29)(30)(31)(32)(33)(34)(35). Childhood socioeconomic status play an important role in determining higher educational attainment, immunisation, health and nutrition which has a signi cant impact in later life (36-39. Particularly, the association between the mother's educational attainment and cognitive functioning is strongly correlated independent of adult socioeconomic status (30).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies investigated health inequalities among MOAs [ 9 ]. Considering the full-fledged effect of socioeconomic status on health begin to take place from midlife, and epidemiological studies set the 45-year-old as a starting point of the midlife [ 10 , 11 , 12 ], this study investigated Seoul residents whose age were 45 or plus.…”
Section: Introductionmentioning
confidence: 99%